Manifestation of Hepatitis C Virus Infection Positively Associated with Gallstones in Patients with Diabetes Mellitus (Medical Forum Monthly, 2021)
Objective: To determine relationship between HCV infection and Gallstones (GS) in our adult population in Sindh Pakistan.Study Design: Cross sectional and case control study.Place and Duration of Study: This study was conducted at the Liaquat University of Medical and Health Sciences, Jamshoro from June 2016 to May 2018.Materials and Methods: All adult HCV positive patients were included who visited our hospital. Stage of disease, weight, BMI, associated DM (Diabetes Mellitus), ethnicity was noted. We took control groups as well; who were attendants of patients visited our clinic. Those patients who had history of cholecystectomy were excluded. Data was analyzed using SPSS version 22.0.Results: There were seven hundred and sixty-two (762) participants and controls were 295. HCV antibody was positive in 467(61.37%). Four hundred and twenty (55%) were males, of these, 270(64.28%) were HCV antibody positive and 150 (35.72%) were controls, of these 342 (45%) were females, 197 (57.60%) had HCV positive infection and 145 (42.4%) were control. There was a significant (p-value 0.007) difference in mean ages of both cohorts. There was no difference in mean weight and BMI of both groups. In HCV antibody positive (9.4 percent) gallstones was significantly higher (p- value 0.048) than controls (4.0 percent).There were 2 positive HCV males (9.25%, n=270) and 25 positive HCV males (12.69%, n=177) in gallstones; 6 (4.13%), n=145) negatively HCV in males and 20 (13.3%), n=150) negative females.However, hepatic disease severity, increased age, marital status and village residence were major factors in increase of prevalence of gallstones.Conclusion: HCV infections with gallstones are closely correlated in males, while they are not related in females. Gallstones are also found with elevated age and incidence of liver disease.